ACUPUNCTURE AS A METHOD OF TREATMENT TO QUIT SMOKING - Suryawan Ang (LPSDI Bina Patria, 2023)
Smoking is a well-known risk factor for cardiovascular disease, chronic obstructive pulmonary disease, and early cancer-related mortality the significance of smoking's adverse health effects on education, communication, training, and public awareness. Acupuncture therapy, which works on the principles of soothing the shén/mind, removing anxiety, and harmonizing yin and yang, is one strategy that is thought to be able to be used to prevent the increase in smoking behaviour. This study looked at the effectiveness of acupuncture in helping people quit smoking. This research technique uses a case study approach model and is qualitative. With the aid of essential individuals, research subjects were chosen using a purposive technique. Research samples were selected using a purposive technique to assess the issues to be studied in line with the research objectives. Methods for gathering data include interviews, observation, and literature reading. Data organization by categorizing the data, followed by four types of organization: pattern matching, explanation construction, model logic discovery, and time series analysis. The study's findings indicate that using acupuncture to stop smoking can have quick, safe, effective, and noticeable outcomes. Patients' internal solid motivation to quit smoking and support from their environment are the keys to success.